A sodium acetate salt recovery process

By using a double-layer adsorption column process in the sodium acetate recovery process, and using activated carbon with a specific pore size range to adsorb sodium acetate, the problem of small application range of existing methods is solved, and efficient and high purity sodium acetate recovery is achieved.

CN118812347BActive Publication Date: 2025-03-18JIANGSU SAIDELI PHARMA MACHINE +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410955684.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-17
Publication Date
2025-03-18
Estimated Expiration
2044-07-17

AI Technical Summary

Technical Problem

The existing sodium acetate recycling method has a small scope of application and a wide range of steps, making it difficult to effectively recover most waste liquids containing sodium acetate.

Method used

Using a double-layer adsorption column process, activated carbon with a pore size between 100-5000 nm and composite activated carbon with a pore size between 0.7-100 nm is used as adsorption materials, sodium acetate in the waste liquid is absorbed through layer by layer adsorption process, and then desorption, filtering, cooling and spin drying to obtain high-purity sodium acetate salt.

Benefits of technology

The efficient recycling of most sodium acetate waste liquids is achieved, and the obtained sodium acetate salt has high purity, fine particles and low moisture content, which is suitable for a wide range of industrial applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of recycling process, and specifically to a sodium acetate salt recycling process, comprising the following steps: after filtering the waste liquid containing sodium acetate with filter paper with a pore size between 5-50 μm, first injecting into a double-layer adsorption column, taking out the upper material and the lower material in the adsorption column in layers; then adding water to the lower material, heating and desorption, filtering, cooling, crystallizing, and drying to obtain sodium acetate salt; the upper adsorption material of the double-layer adsorption column is activated carbon with a pore size between 100-5000 nm, and the lower layer is a composite activated carbon with a pore size between 0.7-100 nm made of activated carbon and nitric acid; the height ratio of the upper layer to the lower layer material is 1-1.5:3-3.5. The upper adsorption material can adsorb substances such as pigments in various wastewaters; and the lower adsorption material can adsorb most of the sodium acetate in the waste liquid. Therefore, the sodium acetate salt recycling process of the present invention is suitable for most waste liquids containing sodium acetate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recovery processes, and in particular to a sodium acetate recovery process. Background Art

[0002] Sodium acetate is a colorless and odorless crystal that can be weathered in the air and is flammable. It is easily soluble in water, slightly soluble in ethanol, and insoluble in ether. It becomes alkaline when hydrolyzed in water and loses its crystal water at 123°C. Sodium acetate has a wide range of uses. It can be used to produce sodium benzylpenicillin in the pharmaceutical industry, as a mordant in the printing and dyeing industry, and as a buffer for the pH value of the plating solution in the electroplating industry to make the coating crystallize finely. It can also be used as a photographic fixative, a meat preservative, and to produce chemical products such as glacial acetic acid, acetone, acetate, and chloroacetic acid. In the process of extensive application, industrial waste liquid containing a large amount of sodium acetate is often produced, so it is very necessary to recycle the sodium acetate in the industrial waste liquid.

[0003] Patent technology document CN107602373B discloses a method for extracting sodium acetate from furfural production wastewater. The extraction method of the invention is: adding sodium carbonate to the furfural production wastewater with an acetic acid content of 2.5%-3% and a pH value of 1-2.5 discharged from the bottom of the distillation tower for neutralization, filtration, preheating, evaporation, concentration, decolorization, filtration, condensation, crystallization, centrifugation to separate crystalline sodium acetate, and packaging and storage after the crystalline sodium acetate is cooled to room temperature. The invention avoids pipeline blockage and resource waste by adjusting the process steps and process parameters, but the steps are numerous and the scope of application is small.

[0004] Patent technology document CN105601499B discloses a method for separating sodium acetate solution containing sodium sulfate. The separation method of the invention is: dehydrating the solution by evaporation to achieve step-by-step crystallization and separation of sodium sulfate and sodium acetate, through mixed solution preparation, evaporation dehydration, sodium sulfate separation and sodium acetate crystallization steps. The separation method of sodium acetate solution containing sodium sulfate provided by the invention has a relatively good separation effect, but its scope of application is relatively small.

[0005] Therefore, according to the above-mentioned related technologies, it is urgent to develop a sodium acetate salt recovery process. Summary of the invention

[0006] In view of this, the object of the present invention is to provide a sodium acetate salt recovery process to improve the problem that the sodium acetate recovery method in the prior art has a small application range.

[0007] Based on the above purpose, the present invention provides a sodium acetate salt recovery process.

[0008] A sodium acetate salt recovery process comprises the following steps:

[0009] Step S1. First, the waste liquid containing sodium acetate is filtered with filter paper having a pore size between 5 and 50 μm, and then injected into a double-layer adsorption column at a flow rate of 0.5-0.8 m / s, and then the upper layer material and the lower layer material in the adsorption column are taken out respectively, and the effluent is reabsorbed;

[0010] Step S2. adding water to the lower layer material, heating and desorption, and then filtering, cooling, crystallizing, and drying to obtain sodium acetate;

[0011] The upper layer adsorption material of the double-layer adsorption column is activated carbon with a pore size between 100-5000nm, and the lower layer adsorption material is composite activated carbon with a pore size between 0.7-100nm prepared by activated carbon and nitric acid;

[0012] The height ratio of the upper layer and the lower layer of the double-layer adsorption column adsorption material is 1-1.5:3-3.5.

[0013] Preferably, the preparation method of the composite activated carbon is as follows:

[0014] Add the activated carbon to the nitric acid solution, shake at 60-75°C for 22-25h, then filter and wash with distilled water until the pH is 6.7-7, place in a vacuum drying oven at 105-110°C and dry for 47-50h to obtain a composite activated carbon with a pore size between 0.7-100nm.

[0015] Preferably, the concentration of the nitric acid solution is 18.5%-20%.

[0016] Preferably, the mass ratio of the activated carbon to the nitric acid solution is 10-13:100-115.

[0017] Preferably, the regeneration method of the upper layer material in step S1 is as follows:

[0018] Add 5%-8% sodium hydroxide to the upper layer material, soak it at 20-35°C for 15-20 minutes, filter it, and then dry it at 110-125°C for 2-3.5 hours to obtain regenerated activated carbon.

[0019] Preferably, the regeneration method of the lower layer material in step S1 is as follows:

[0020] Deionized water is added to the lower layer material taken out, and the mixture is refluxed at 780-800° C. for 15-20 min, filtered, and then dried at 110-125° C. for 2-3.5 h to obtain regenerated composite activated carbon.

[0021] Preferably, the temperature of the heating desorption in step S2 is 95-98° C. and the time is 45-60 min.

[0022] Preferably, the cooling temperature in step S2 is 35-50°C.

[0023] Preferably, the temperature during the spin drying in step S2 is 20-35°C.

[0024] Beneficial effects of the present invention:

[0025] The present invention provides a sodium acetate salt recovery process. The selected adsorption materials of each layer in the double-layer adsorption column used in the present invention can progressively adsorb various substances in waste liquids, wherein the upper adsorption material can adsorb substances such as pigments in various wastewaters, and the phosphoric acid-compounded activated carbon material of the lower layer can adsorb sodium acetate in the waste liquid. Subsequently, only the lower layer material needs to be desorbed, filtered, cooled, and other steps to obtain sodium acetate salt with high purity; and the adsorption materials of each layer of the self-made double-layer adsorption column can be recycled after regeneration treatment. Therefore, the sodium acetate salt recovery process of the present invention is suitable for most waste liquids containing sodium acetate. DETAILED DESCRIPTION

[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1: A recovery process of sodium acetate, the specific steps are as follows:

[0028] Step S1. Add 10 g of activated carbon to 100 g of 18.5% nitric acid solution, shake at 60° C. for 22 h, filter, wash with distilled water until pH = 6.7, and dry in a vacuum drying oven at 105° C. for 47 h to obtain a composite activated carbon with a pore size between 0.7 and 100 nm;

[0029] Step S2. Add composite activated carbon with a pore size between 0.7-100 nm into the separation column and compact it, then add activated carbon with a pore size between 100-5000 nm and compact it, the height ratio of the composite activated carbon with a pore size between 0.7-100 nm and the activated carbon with a pore size between 100-5000 nm is 1:3, and a double-layer adsorption column is obtained.

[0030] Step S3. First, the waste liquid containing sodium acetate is filtered with filter paper having a pore size between 5 and 50 μm, and then injected into a double-layer adsorption column at a flow rate of 0.5 m / s. After the adsorption column reaches the saturation point, the upper layer material and the lower layer material in the adsorption column are taken out in layers, and the effluent is reabsorbed;

[0031] Step S4. Add water to the adsorbent material in the lower layer, soak it at 95°C for 45 minutes for desorption, filter it, cool it at 35°C, crystallize it, and spin-dry it at 20°C to obtain sodium acetate;

[0032] Embodiment 2: A recovery process of sodium acetate, the specific steps are as follows:

[0033] Step S1. Add 11 g of activated carbon to 105 g of 19% nitric acid solution, shake at 65° C. for 23 h, filter, wash with distilled water until pH = 6.8, and dry in a vacuum drying oven at 106° C. for 48 h to obtain a composite activated carbon with a pore size between 0.7 and 100 nm;

[0034] Step S2. Add composite activated carbon with a pore size between 0.7-100 nm into the separation column and compact it, then add activated carbon with a pore size between 100-5000 nm and compact it, the height ratio of the composite activated carbon with a pore size between 0.7-100 nm and the activated carbon with a pore size between 100-5000 nm is 1.1:3.1, and a double-layer adsorption column is obtained.

[0035] Step S3. First, the waste liquid containing sodium acetate is filtered with filter paper having a pore size between 5 and 50 μm, and then injected into a double-layer adsorption column at a flow rate of 0.6 m / s. After the adsorption column reaches the saturation point, the upper layer material and the lower layer material in the adsorption column are taken out in layers, and the effluent is reabsorbed;

[0036] Step S4. Add water to the adsorption material of the lower layer, soak it at 96°C for 50 minutes for desorption, then filter it, cool it at 40°C, crystallize it, and spin-dry it at 25°C to obtain sodium acetate;

[0037] Embodiment 3: A recovery process of sodium acetate, the specific steps are as follows:

[0038] Step S1. Add 12 g of activated carbon to 110 g of 19.5% nitric acid solution, shake at 70°C for 24 h, filter, wash with distilled water until pH = 6.9, and dry in a vacuum drying oven at 108°C for 49 h to obtain a composite activated carbon with a pore size between 0.7 and 100 nm;

[0039] Step S2. Add composite activated carbon with a pore size between 0.7-100 nm into the separation column and compact it, then add activated carbon with a pore size between 100-5000 nm and compact it, the height ratio of the composite activated carbon with a pore size between 0.7-100 nm and the activated carbon with a pore size between 100-5000 nm is 1.4:3.4, and a double-layer adsorption column is obtained.

[0040] Step S3. First, the waste liquid containing sodium acetate is filtered with filter paper having a pore size between 5 and 50 μm, and then injected into a double-layer adsorption column at a flow rate of 0.7 m / s, and the upper layer material and the lower layer material in the adsorption column are taken out in layers, and the effluent is reabsorbed;

[0041] Step S4. Add water to the adsorption material of the lower layer, soak it at 97°C for 55 minutes for desorption, then filter it, cool it at 45°C, crystallize it, and spin-dry it at 30°C to obtain sodium acetate;

[0042] Embodiment 4: A recovery process of sodium acetate, the specific steps are as follows:

[0043] Step S1. Add 13 g of activated carbon to 115 g of 18.5% nitric acid solution, shake at 75°C for 25 h, filter, wash with distilled water until pH = 7, and dry in a vacuum drying oven at 110°C for 50 h to obtain a composite activated carbon with a pore size between 0.7 and 100 nm;

[0044] Step S2. Add composite activated carbon with a pore size between 0.7-100 nm into the separation column and compact it, then add activated carbon with a pore size between 100-5000 nm and compact it, the height ratio of the composite activated carbon with a pore size between 0.7-100 nm and the activated carbon with a pore size between 100-5000 nm is 1.5:3.5, and a double-layer adsorption column is obtained.

[0045] Step S3. First, the waste liquid containing sodium acetate is filtered with filter paper having a pore size between 5 and 50 μm, and then injected into a double-layer adsorption column at a flow rate of 0.8 m / s, and each layer of adsorption material in the adsorption column is removed in layers, and the effluent is reabsorbed;

[0046] Step S4. adding water to the lower layer material, and soaking at 98°C for 60 minutes for desorption, then filtering, cooling at 50°C, crystallizing, and drying at 35°C to obtain sodium acetate;

[0047] Comparative Example 1:

[0048] Compared with Example 1, this comparative example only replaces the "composite activated carbon with a pore size between 0.7-100 nm" with "activated carbon with a pore size between 0.7-100 nm", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally sodium acetate is obtained.

[0049] Comparative Example 2:

[0050] Compared with Example 1, this comparative example only replaces "the height ratio of the composite activated carbon with a pore size between 0.7-100nm and the activated carbon with a pore size between 100-5000nm is 1.1:3.1" with "the height ratio of the composite activated carbon with a pore size between 0.7-100nm and the activated carbon with a pore size between 100-5000nm is 3.1:1.1", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and sodium acetate is finally obtained.

[0051] Comparative Example 3:

[0052] Compared with Example 1, this comparative example only replaces "spin drying at 20°C" with "centrifugal separation at 20°C", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally sodium acetate is obtained.

[0053] Performance Testing:

[0054] The performance test of the sodium acetate recovered in Examples 1 to 4 and Comparative Examples 1 to 3 was performed:

[0055] Test of sodium acetate recovery rate:

[0056] According to GB / T964-2015 Chemical Reagents - Anhydrous Sodium Acetate standard, take 25g of wastewater containing sodium acetate, filter it, inject it into a strong acid cation exchange resin column, exchange it at a flow rate of 5mL / min, collect the exchange liquid in a conical flask, wash the resin with water several times until the dripping solution is neutral, collect the washing liquid in the conical flask containing the exchange liquid, add 2 drops of 10g / L phenolphthalein indicator solution to the conical flask, and then titrate with 0.1mol / L sodium hydroxide until the solution is pink and does not change within 30s. color, and do a blank experiment at the same time; then calculate the content of sodium acetate in the wastewater according to the following sodium acetate content calculation formula; recover the sodium acetate salt obtained by 25g of waste liquid in Example 1-Example 4 and Comparative Example 1-Comparative Example 3, and test the content of the obtained sodium acetate salt. Under the same test conditions, measure three times in a row, and take the average value as the content of sodium acetate (g); then calculate the recovery rate (%) of the recovery process of Example 1-Example 4 and Comparative Example 1-Comparative Example 3 according to the sodium acetate recovery rate calculation formula;

[0057] Sodium acetate content calculation formula:

[0058] Wherein, V1 is the volume of sodium hydroxide used for titration, in mL, V2 is the volume of sodium hydroxide used for blank experiment titration, in mL, and M is the molar mass of sodium acetate, in g / mL.

[0059] Sodium acetate recovery rate calculation formula:

[0060] Among them, m0 is the content of sodium acetate in the waste liquid, in g, and m1 is the content of sodium acetate in the sodium acetate salt recovered from the waste liquid, in g.

[0061] Particle size test:

[0062] Referring to GB / T13025.1-2012 "General Test Methods for Salt Manufacturing Industry - Determination of Particle Size" standard, 100g of sodium acetate was taken, and a test sieve with a pore size of 0.75mm was used for manual sieving for 2min. The mass m1g of sodium acetate on the sieve was weighed, and the particle size of sodium acetate was calculated according to the following formula; the sodium acetate salts recovered in Examples 1 to 4 and Comparative Examples 1 to 3 were tested for particle size. Under the same test conditions, the measurements were performed three times in a row, and the average value was taken as the particle size (%) of sodium acetate;

[0063] Particle size calculation formula:

[0064] Whiteness test:

[0065] Referring to GB / T13025.2-2008 "General Test Methods for Salt Making Industry - Determination of Whiteness", the sample box was filled with sodium acetate and filled, and after the sample was pressed, the sodium acetate salt recovered in Example 1 to Example 4 and Comparative Example 1 to Comparative Example 3 was tested for whiteness using a calibrated automatic whiteness meter (WSD-3C, Beijing Kangxue Optical Instrument Co., Ltd.). Under the same test conditions, three consecutive measurements were performed, and the average value was taken as the whiteness (%) of sodium acetate;

[0066] Water content test:

[0067] Referring to GB / T13025.3-2012 "General Test Methods for Salt Making Industry - Determination of Water Content", the crushed sodium acetate with a mass of m was moved into a dry and weighed weighing bottle (mass of m0) at 80-90°C, the weighing bottle cap was opened obliquely, and it was placed in a constant temperature drying oven (DHG-907385-Ⅲ, Shanghai Xinmiao Medical Equipment Manufacturing Co., Ltd.), dried at 110-130°C for 2h, covered with the weighing bottle cap, taken out, moved into a dryer, cooled to room temperature and weighed, and then weighed once every 1h of drying until the difference in mass between two consecutive weighings does not exceed 0.0005g, which is regarded as constant weight (m1). The water content of sodium acetate can be obtained by processing the data according to the following formula. The sodium acetate salt recovered in Examples 1-4 and Comparative Examples 1-3 was tested for water content. Under the same test conditions, three consecutive measurements were made, and the average value was taken as the water content (%) of sodium acetate;

[0068] Moisture content calculation formula:

[0069] Table 1

[0070] project Sodium acetate recovery rate / % granularity / % Whiteness / % Water content / % Example 1 88.7 5.6 88 0.005 Example 2 89.0 5.4 89 0.004 Example 3 89.2 5.5 85 0.005 Example 4 89.0 5.4 89 0.006 Comparative Example 1 71.1 5.8 81 0.010 Comparative Example 2 77.5 5.9 87 0.009 Comparative Example 3 86.6 25.1 78 0.087

[0071] Data Analysis:

[0072] As can be seen from Table 1, the sodium acetate recovery rate of the process for recovering sodium acetate of the present invention is the highest, and the particle size and water content of the recovered sodium acetate salt are relatively small and the whiteness is high.

[0073] This may be because the layers of selected adsorption materials in the double-layer adsorption column used in the present invention can progressively adsorb various substances in the waste liquid, wherein the upper layer of relatively large-aperture activated carbon can adsorb substances such as pigments and macromolecules in the waste water, thereby improving the whiteness of the obtained sodium acetate salt; and the phosphoric acid-compounded activated carbon material in the lower layer can adsorb the vast majority of sodium acetate in the waste liquid, thereby improving the recovery rate of sodium acetate, and only the lower layer material needs to be desorbed, filtered, and dried to obtain a sodium acetate salt with a higher purity; the drying process can make the crystallized sodium acetate crystals rub, collide and dehydrate with each other, so that the obtained sodium acetate salt particles can be made finer and drier. Therefore, the sodium acetate recovery process of the present invention has the highest sodium acetate recovery rate, and the particle size and water content of the recovered sodium acetate salt are relatively small and the whiteness is high.

[0074] In Comparative Example 1, "composite activated carbon with a pore size of 0.7-100 nm" is replaced by "activated carbon with a pore size of 0.7-100 nm". It can be seen from Table 1 that the recovery rate of sodium acetate is greatly reduced compared with Example 1. This may be because the activated carbon with a pore size of 0.7-100 nm that has not been compounded with phosphoric acid cannot adsorb sodium ions well, so its recovery rate of sodium acetate is low; Comparative Example 2 replaces "the height ratio of the composite activated carbon with a pore size of 0.7-100 nm to the activated carbon with a pore size of 100-5000 nm is 1.1:3.1" with "the composite activated carbon with a pore size of 0.7-100 nm and the activated carbon with a pore size of 100-5000 nm is 1.1:3.1". -5000nm activated carbon height ratio is 3.1:1.1". It can be seen from Table 1 that compared with Example 1, the sodium acetate recovery rate is significantly reduced. This may be due to the reduction of the lower layer material in the double-layer adsorption column, resulting in the incomplete adsorption of sodium ions in some waste liquids. Therefore, the sodium acetate recovery rate of Comparative Example 2 is reduced; Comparative Example 3 replaces "drying at 20°C" with "centrifugal separation at 20°C". It can be seen from Table 1 that compared with Example 1, the fineness and water content of the recovered sodium acetate salt have been greatly improved. This may be due to the fact that compared with the centrifugal separation process, the crystallized sodium acetate crystals in the drying process have been rubbing, colliding and dehydrating with each other, which can make the obtained sodium acetate salt particles finer and drier.

[0075] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

[0076] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A sodium acetate recovery process, characterized in that: The following steps are involved: Step S1. First, the waste liquid containing sodium acetate is filtered with filter paper having a pore size between 5 and 50 μm, and then injected into a double-layer adsorption column at a flow rate of 0.5-0.8 m / s, and then the upper layer material and the lower layer material in the adsorption column are taken out respectively, and the effluent is reabsorbed; Step S2. adding water to the lower layer material, heating and desorption, and then filtering, cooling, crystallizing, and drying to obtain sodium acetate; The upper layer adsorption material of the double-layer adsorption column is activated carbon with a pore size between 100-5000nm, and the lower layer adsorption material is composite activated carbon with a pore size between 0.7-100nm prepared by activated carbon and nitric acid; The height ratio of the upper layer and the lower layer of the double-layer adsorption column adsorption material is 1-1.5:3-3.5; The preparation method of the composite activated carbon is as follows: Add activated carbon to nitric acid solution, oscillate at 60-75°C for 22-25h, then filter, wash with distilled water to pH=6.7-7, put into a vacuum drying oven at 105-110°C for 47-50h, and obtain composite activated carbon with a pore size between 0.7-100nm; wherein the concentration of the nitric acid solution is 18.5%-20%; the mass ratio of the activated carbon to the nitric acid solution is 10-13:100-115.

2. A sodium acetate salt recovery process according to claim 1, characterized in that, The regeneration method of the upper layer material in step S1 is as follows: Add 5%-8% sodium hydroxide to the upper material, soak it at 20-35°C for 15-20 minutes, filter it, and then dry it at 110-125°C for 2-3.5 hours to obtain regenerated activated carbon.

3. A sodium acetate salt recovery process according to claim 1, characterized in that, The temperature of the heating desorption in step S2 is 95-98° C. and the time is 45-60 min.

4. A sodium acetate recovery process according to claim 1, characterized in that, The temperature during cooling in step S2 is 35-50°C.

5. A sodium acetate recovery process according to claim 1, characterized in that, The temperature during the spin drying in step S2 is 20-35°C.

Citation Information

Patent Citations

  • A method for extracting sodium acetate from furfural production wastewater

    CN107602373B

  • A kind of separation method of sodium acetate solution containing sodium sulfate

    CN105601499B

  • Method of extracting sodium acetate from furfural production wastewater

    CN107602373A